1996
DOI: 10.1111/j.1751-1097.1996.tb02475.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Biological Testing of Photobleaching of Porphyrins in Solutions*

Abstract: The photobleaching of protoporhyrin IX (PP IX) and hematoporphyrin derivative (HpD) solutions was followed using three different methods: spectrophotometry, fluorometry and photodynamically induced cytotoxicity. The latter entails photoirradiation of HT29 human colon adenocarcinoma cells in the presence of preirradiated solutions of HpD and PP IX (lambda < or = 415 nm). The highest cytotoxicity was observed in the presence of unirradiated dye and decreased with the time of preirradiation. This decay in photocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 25 publications
1
35
0
2
Order By: Relevance
“…Photobleaching rates depend strongly on the aggregation state of photosensitizers. It has been shown that photodegradation of porphyrins is much faster for monomerised photosensitizers 20–22. The probable explanation could be related to the limited oxygen availability deep in the clusters of the aggregated species, thus explaining their weak photobleaching 16, 23…”
Section: Resultsmentioning
confidence: 99%
“…Photobleaching rates depend strongly on the aggregation state of photosensitizers. It has been shown that photodegradation of porphyrins is much faster for monomerised photosensitizers 20–22. The probable explanation could be related to the limited oxygen availability deep in the clusters of the aggregated species, thus explaining their weak photobleaching 16, 23…”
Section: Resultsmentioning
confidence: 99%
“…Considering the photobleaching of porphyrins during irradiation (Rotomski et al, 1996;Bezdetnaya et al, 1996;Moan et al, 1997), a threshold concentration of PpIX necessary for tissue destruction, and the high selectivity of h-ALA-induced PpIX, a small PpIX amount in healthy areas of the bladder, observed in this study will probably not induce any damage in these regions. However, the twofold increase of PpIX fluorescence after 6 h in neoplastic tissues by using h-ALA may further enhance the PDT effect as compared to the use of ALA.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of chlorine atoms in the structure of ACS769F4 allows the increase of the singlet quantum yield of 1 O 2 by the heavy atom effect (23) and the stability of the porphyrin. Although different environmental conditions are expected in biological systems (24) these are important properties for a photosensitizer.…”
Section: Synthesis Properties and Photobleaching Of Acs769f4mentioning
confidence: 99%